Panorama Should Pay - Unknown (Daily Express)
In this editorial, it states that the marriage of convenience between the government-sponsored Carnival Development Committee and Pan Trinbago, which represents steelbands, is an uneasy one. A formula must be found and Panorama should be regarded as a business enterprise so that government would not dare deny some form of assistance to a well-run Panorama.
Keywords: Steel bands (Music) -- Administration -- Trinidad and Tobago; Panorama (Musical festival); Pan Trinbago (Organization); Steel bands (Music) -- Competitions -- Trinidad and Tobago